Prevalence rate trends of borderline personality disorder symptoms and self-injurious behaviors in college students from 2017 to 2021 - Min, Jiwon; Hein, Katherine E.; Medlin, Austin R.; Mullins-Sweatt, Stephanie N. (Psychiatry research, 2023)
•There is an increasing trend of NSSI rates and BPD symptoms among college students.•There is a significant increase in odds of elevated BPD symptoms, with steeper increases in female students.•There is a significant increase in odds of increased NSSI behaviors over time. The current study examines the prevalence rates of borderline personality disorder (BPD) symptoms and nonsuicidal self-injury (NSSI) behaviors amongst college students over a five-year period, including pre- and during the COVID pandemic. Online prescreener surveys were completed by undergraduate students (n = 12,756) attending a large Southern Plains University every semester from Spring of 2017 to Spring of 2021. The percentage of students with NSSI history and significant BPD symptoms were visualized by semester to examine trends over time. A series of logistic regressions and negative binomial regressions were conducted on NSSI history and BPD symptoms to examine whether the endorsement rates have been increasing over time and to compare before and during COVID pandemic. There was an increasing trend of NSSI rates and significant BPD symptoms over time for all sexes. Furthermore, there was a steeper increase in BPD symptoms specifically in female students over the last five years. Additionally, there was a significant increase in odds of elevated BPD symptoms and NSSI behaviors in the college students enrolled during the COVID pandemic compared with pre-COVID. Overall, there has been an increasing trend in BPD symptoms and NSSI rates over the last few years, including during the COVID pandemic.